Phubbing Sebagai Tantangan Etika Komunikasi: Dampaknya terhadap Kesejahteraan Emosional dalam Hubungan Personal - Aulia Nurul Khasanah; Rohmah Lulu Fitriani; Sevilla Permatawati; Siti Nur Azizah; Muslikah Muslikah; Ashari Mahfud (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The widespread use of smartphones has given rise to the phenomenon of phubbing, where individuals prioritize their devices over face-to-face interactions. The purpose of this study is to explore phubbing as a communication ethics challenge and its impact on emotional well-being in personal relationships. The method used in this study is a literature review involving national and international indexed journals obtained through Google Scholar, Directory of Open Access Journals (DOAJ), and ERIC (Educational Resources Information Center), Taylor & Francis, Springer, Elsevier with a span of 2017-2024. The findings of this study reveal that phubing can have a negative impact on interpersonal relationships and individual psychological well-being. This behavior can damage communication, reduce the quality of personal relationships, and trigger psychological problems such as anxiety, depression, and feelings of loneliness. Therefore, interventions in guidance and counseling are needed to deal with phubbing more comprehensivel.